1995
DOI: 10.1016/0029-7844(95)00179-u
|View full text |Cite
|
Sign up to set email alerts
|

The association between polyhydramnios and preterm delivery

Abstract: The underlying cause of polyhydramnios, rather than the relative excess of amniotic fluid as defined by this study, appears to determine when preterm labor will occur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
50
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(57 citation statements)
references
References 8 publications
6
50
1
Order By: Relevance
“…It should be noted that this percentage is lower (10% to 15%) in normal singleton pregnancies (13)(14)(15). As stated previously, there was no case of preterm delivery in our work.…”
Section: Discussionsupporting
confidence: 39%
See 1 more Smart Citation
“…It should be noted that this percentage is lower (10% to 15%) in normal singleton pregnancies (13)(14)(15). As stated previously, there was no case of preterm delivery in our work.…”
Section: Discussionsupporting
confidence: 39%
“…However, Many et al found that underlying causes of polyhydramnios and not the volume of amniotic fluid is a major factor associated with preterm delivery so that in idiopathic cases the risk of preterm birth has been less than cases with underlying causes of polyhydramnios (14).…”
Section: Discussionmentioning
confidence: 99%
“…In 358 pregnant women with polyhydramnios, Queenan and Gadow [2]found that 24.6% had diabetes mellitus, 11.5% had erythroblastosis fetalis, 8.4% had multiple births, 1.5% had acute polyhydramnios, and 20% had congenital anomalies; in 34% of these cases polyhydramnios was idiopathic. However, few studies were performed on the relationship between polyhydramnios and congenital anomalies and most of them were on at risk pregnancies [3, 4, 5, 6, 7, 8, 9, 10, 11]. Since the landmark report of Queenan and Gadow [2], the definition of polyhydramnios has shifted from a clinical to an ultrasonographic one.…”
Section: Introductionmentioning
confidence: 99%
“…al. (1995) [7] reported that 20% of 275 women with an AFI of 25 cm delivered preterm and it were more common with anomalous fetus 40%. Malpresentation was seen in three cases (10%) in this study two cases were seen in severe polyhydramnios one was breech and the other was compound presentation.…”
Section: Discussionmentioning
confidence: 99%